Pembangunan Pariwisata Berkelanjutan: Studi tentang Pengembangan Wisata Gua Selomangleng di Kota Kediri - Heylen Amildha Yanuarita (Universitas Muhammadiyah Gorontalo, 2018)
This article aims to determine the extent of the development of Selomangleng Cave in the City of Kediri in the perspective of sustainable tourism development. In this study the researcher used a qualitative descriptive method in which the researcher elaborated, described, explained, concerning matters related to the development of Selomangleng Cave tourism objects, as well as the development implications, challenges ahead in the perspective of sustainable development. The results of this study concluded that the development of the Selomangleng Cave of the City of Kediri was still very minimal, constrained by the issue of land ownership, however there was still an effort to develop Selomangleng Cave tourism in accordance with the principles of sustainable development. Artikel ini bertujuan untuk mengetahui sejauh mana pengembangan Gua Selomangleng di Kota Kediri dalam perspektif pembangunan pariwisata berkelanjutan. Dalam penelitian ini Peneliti menggunakan metode deskriptif kualitatif dimana peneliti menguraikan, menggambarkan, menjelaskan, mengenai hal-hal yang terkait dengan pengembangan obyek pariwisata Gua Selomangleng, serta implikasi pengembangan, tantangan kedepan dalam perspektif pembangunan berkelanjutan. Hasil penelitian ini menyimpulkan bahwa pengembangan wisata Gua Selomangleng Kota Kediri masih sangat minim, terkendala dengan persoalan kepemilikan lahan, namun demikian tetap ada usaha pengembangan wisata Gua Selomangleng yang sesuai dengan prinsip pembangunan berkelanjutan.